IOT RIVER POLLUTION MONITORING SYSTEM USING LORA - Abdul Razak, Muhammad Sallehuddin Yusof (Universiti Teknologi PETRONAS, 2021)
A robust river water quality monitoring system is important to collect crucial data sets that shows the health of our local rivers and determine any pollution present. These data sets are necessary to determine the most proactive action to maintain the river ecosystem, depending on the levels of pollution. Current methods make use of sophisticated river monitoring stations and manual in-situ water quality testing, which poses equipment and labour cost when deployed in large numbers. This project aims to present a method of developing a low-cost, low-power water quality monitoring device capable of long-range communication to a cloud analytic service with LoRa technology. The device proposed acts as a LoRa sensor node equipped with three water quality sensors measuring turbidity, total dissolved solids (TDS), and temperature, respectively.